2016
DOI: 10.1016/j.virol.2016.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Cellular minichromosome maintenance complex component 5 (MCM5) is incorporated into HIV-1 virions and modulates viral replication in the newly infected cells

Abstract: The post-entry events of HIV-1 infection occur within reverse transcription complexes derived from the viral cores entering the target cell. HIV-1 cores contain host proteins incorporated from virus-producing cells. In this report, we show that MCM5, a subunit of the hexameric minichromosome maintenance (MCM) DNA helicase complex, associates with Gag polyprotein and is incorporated into HIV-1 virions. The progeny virions depleted of MCM5 demonstrated reduced reverse transcription in newly infected cells, but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…This included two members of the mini chromosome maintenance (MCM) family. Expression of MCM5 has been shown to inhibit HIV infection (Santos et al, 2016), suggesting that its reduction in infected cells would benefit virus replication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This included two members of the mini chromosome maintenance (MCM) family. Expression of MCM5 has been shown to inhibit HIV infection (Santos et al, 2016), suggesting that its reduction in infected cells would benefit virus replication.…”
Section: Resultsmentioning
confidence: 99%
“…Several factors were identified with altered levels in more than one fraction, suggesting changes in localization. This included the MCM complex which has been shown to inhibit HIV infection (Santos et al, 2016), and CypB, which we recently demonstrated potentiates HIV transduction (DeBoer et al, 2016). Further studies with other candidate proteins may identify additional factors that alter HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The replication of the influenza virus is regulated by the MCM complex [27]. MCM5 is incorporated into HIV-1 virions and regulates HIV replication via association with the Gag polyprotein [28]. The pre-replicative complex (pre-RC), including MCM2-7, is recruited to the Epstein-Barr virus (EBV) replication origin, oriP [24], and Kaposi's sarcoma-associated herpesvirus (KSHV) oriP [29] during latency.…”
Section: Discussionmentioning
confidence: 99%